Designing Knit Designers - Motta, Martina (Design International - Open Access, 2019)
"Traditionally associated with craftmanship and manual work, knitwear seems a quite unusual subject of investigation for scientific research. This book places it as an integrative part of the industrial design culture where the dialogue between a productive system of excellence and the design discipline taught in universities becomes a topic of central concern. From an industrial standpoint, knitwear is a fertile ground of technological experimentation while being at the same time one of the most traditional sectors of Made in Italy. The complexity of a long and fragmented production chain is an interesting challenge for designers but affects the training and the knowledge transfer inside companies. On the academic side, the presence of such an industry creates the urgency for higher education to understand how to train knit designers as new professionals, and thus the opportunity for knitwear to be recognized as a discipline deserving specific teaching strategies and a focused scientific research. The present book reports an experimentation conducted in the unique conditions of the Italian industrial design culture, that defined tools and methods to train knit designers not as artists, but with the technical and cultural knowledge and the project-oriented mindset that is typical of industrial design disciplines. These contents are of interest for the academy, as they constitute a tool to design teaching experiences oriented to such a specific industrial sector; for those approaching knitwear design, as it is a pool of information on the complexity of knitwear, a map of the background knowledge, collected and rearranged, and a compass to be guided in building one's own skills; for professionals, who will find here their history, the opinions of colleagues, the opportunity to integrate their knowledge and to learn more about the in-depth experimental, technical and design work that takes place at Politecnico di Milano."